2014
DOI: 10.1371/journal.pone.0094829
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Allosteric Effectors Based on the Predicted Allosteric Sites for Escherichia coli D-3-Phosphoglycerate Dehydrogenase

Abstract: D-3-phosphoglycerate dehydrogenase (PGDH) from Escherichia coli catalyzes the first critical step in serine biosynthesis, and can be allosterically inhibited by serine. In a previous study, we developed a computational method for allosteric site prediction using a coarse-grained two-state Gō Model and perturbation. Two potential allosteric sites were predicted for E. coli PGDH, one close to the active site and the nucleotide binding site (Site I) and the other near the regulatory domain (Site II). In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…PHGDH was immobilized on a CM5 sensor chip by using standard amine-coupling at 25°C with 1× running buffer PBS-P (GE Healthcare), as described previously (Wang et al, 2014). For details, see the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PHGDH was immobilized on a CM5 sensor chip by using standard amine-coupling at 25°C with 1× running buffer PBS-P (GE Healthcare), as described previously (Wang et al, 2014). For details, see the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Computational methods for rational design of allosteric effectors were emerging (Wagner et al, 2016; Ma et al, 2016) and a number of successful application examples have been reported. For example, using the two-state Go model based allosteric site prediction method that we developed (Qi et al, 2012), we obtained novel allosteric inhibitors for Escherichia coli ( E. coli ) phosphoglycerate dehydrogenase (Wang et al, 2014). Novel enzymes activators were also found using combined computational and experimental approach (Meng et al, 2016), providing an alternative way to control disease-related molecular networks (Pei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These results and many others (e.g., Refs. ) have suggested that surface‐exposed network residues may serve as druggable interfaces for allosteric modulators.…”
Section: Enzymes As Amino Acid Interaction Networkmentioning
confidence: 99%
“…In other cases, the effect is dependent on the interaction between the allosteric ligand and protein. Modifications of the allosteric ligand may change the effect from activation to inhibition, and sometimes the effect is even concentration dependent …”
Section: Resultsmentioning
confidence: 99%